Integrating Technology in Organizational Communication to Advance Progressive Islamic Values: Insights from Muhammadiyah - Sumarlan, Iman; Muktiyo, Widodo; Pawito, Pawito; Rahmanto, Andre Noevi (UNIMUS Web Conferences, 2025)
This study examines the role of organizational communication within Muhammadiyah in shaping and sustaining the discourse of Islam Berkemajuan, which emphasizes the values of moderation and progressiveness in Islamic teachings. The implementation of digital media usage is a key focus, particularly through the utilization of communication technologies to reach a broader audience, including the youth who are actively engaged in the digital learning ecosystem. Muhammadiyah integrates social media and other digital platforms as strategic tools to align vertical and horizontal communication. This digital communication not only provides access to educational resources based on progressive values but also facilitates two-way interactions that encourage active engagement. This qualitative study explores how communication shapes and sustains the structure and practices of the organization. Data was collected through in-depth interviews with Muhammadiyah leaders, observation of organizational activities, and analysis of related documents. A thematic analysis approach was used to identify communication patterns that support the dissemination and sustainability of Islam Berkemajuan. The findings indicate that the use of technology in Muhammadiyah’s organizational communication strengthens the relevance and impact of Islam Berkemajuan values amid the challenges of the digital era. In conclusion, effective communication strategies through digital media are crucial for Muhammadiyah to re-main relevant in spreading progressive Islamic values. By adaptively integrating technology, Muhammadiyah has successfully strengthened its organizational identity while addressing contemporary social and cultural challenges. This study provides significant contributions to the development of organizational communication practices based on Islamic values.